Peran Kualitas Layanan dan Kepercayaan pada Loyalitas dengan Kepuasan Nasabah Sebagai Variabel Intervening pada KSP. Perkasa Djaya Mandiri Jemer - Firdaus, Raihul; Herlambang, Toni; Qomariah, Nurul (BUDGETING : Journal of Business, Management and Accounting, 2023)
The aim of this research is to determine directly or indirectly the influence of service quality and trust on loyalty through customer satisfaction as an intervening variable in KSP. Perkasa Djaya Mandiri Jember. The data analysis method in this research uses quantitative methods using WarpPLS 7.0. The results of data analysis show that service quality and trust have a positive and significant effect on customer loyalty through satisfaction. It can be concluded that service quality and trust have a positive and significant effect on customer loyalty through satisfaction. Keywords: Loyalty, Service, Trust, Satisfaction